Future spot gas prices in the US and the UK: are movements more influenced by country factors or by global factors? - Simpson, John (Incisive Media, 2011)
This paper highlights the importance of gas futures (country factors) and oil futures (global factors)for explaining the future spot gas price, with a comparative focus on the major Western gas markets of the United States and the United Kingdom. These markets are known to have achieved (to a relatively high degree) a decoupling of gas and oil prices over the past two decades. The markets are tested with lagged daily data over the period from late 2003 to late 2009. Insight into the scope for further deregulation of country gas markets is provided. The evidence shows that both markets have made strong progress in deregulation, but that international and domestic arbitrage opportunities remain between gas and oil, particularly in the UK gas market.